Microspore-derived embryos from Quercus suber anthers mimic zygotic embryos and maintain haploidy in long-term anther culture. (Journal of plant physiology, 2003)
Microspore-derived embryos produced from cork oak anther cultures after long-term incubations (up to 10-12 months) were analysed in order to determine the genetic variability and ploidy level stability, as well as morphology, developmental pattern and cellular organisation. Most of the embryos from long-term anther cultures were haploid (90.7%), corresponding to their microspore origin. The presence of a low percentage of diploid embryos (7.4%) was observed. Microsatellite analysis of haploid embryos, indicated different microspores origins of the same anther. In the diploid embryos, homozygosity for different alleles was detected from anther wall tissues, excluding the possibility of clonal origin. The maintenance of a high proportion of haploid embryos, in long-term anther cultures, is similar in percentage to that reported in embryos originating after 20 days of plating (Bueno et al. 1997). This suggests that no significant alterations in the ploidy level occurred during long incubations (up to 12 months). These results suggest that ploidy changes are rare in this in vitro system, and do not significantly increase during long-term cultures. Microscopical studies of the microspore embryos in various stages revealed a healthy and well developed anatomy with no aberrant or chimeric structures. The general morphology of embryos appearing at different times after plating, looked similar to that of earlier embryos, as well as the zygotic embryos, indicating that they represent high quality material for cork oak breeding.

Microspore-derived embryos from Quercus suber anthers mimic zygotic embryos and maintain haploidy in long-term anther culture. - Bueno, María a; Gomez, Arancha; Sepulveda, Federico; Seguí, José M.; Testillano, Pilar S.; Manzanera, Jose a; Risueño, Maria-Carmen (Journal of plant physiology, 2003)
Microspore-derived embryos produced from cork oak anther cultures after long-term incubations (up to 10-12 months) were analysed in order to determine the genetic variability and ploidy level stability, as well as morphology, developmental pattern and cellular organisation. Most of the embryos from long-term anther cultures were haploid (90.7%), corresponding to their microspore origin. The presence of a low percentage of diploid embryos (7.4%) was observed. Microsatellite analysis of haploid embryos, indicated different microspores origins of the same anther. In the diploid embryos, homozygosity for different alleles was detected from anther wall tissues, excluding the possibility of clonal origin. The maintenance of a high proportion of haploid embryos, in long-term anther cultures, is similar in percentage to that reported in embryos originating after 20 days of plating (Bueno et al. 1997). This suggests that no significant alterations in the ploidy level occurred during long incubations (up to 12 months). These results suggest that ploidy changes are rare in this in vitro system, and do not significantly increase during long-term cultures. Microscopical studies of the microspore embryos in various stages revealed a healthy and well developed anatomy with no aberrant or chimeric structures. The general morphology of embryos appearing at different times after plating, looked similar to that of earlier embryos, as well as the zygotic embryos, indicating that they represent high quality material for cork oak breeding.
The following values have no corresponding Zotero field: accession-num: 12964871
Keywords: Cytochemistry; DNA-Analysis; flow cytometry; haploid embryos; immunocyto- chemistry; Quercus suber L.